Dynamic changes in cortical neurotrophic factor-positive interneurons during sleep - Christine M. Muheim; Marcos G. Frank (Scientific Reports)
Abstract Mammalian sleep is characterized by profound changes in the activity of cortical neurons which sum to electroencephalographic (EEG) rhythms linked to sleep regulation and function. Inhibitory interneurons (INs) influence these rhythms via direct inhibition of excitatory neurons and disinhibition that arises from IN–IN interactions. Therefore, understanding the activity of different classes of INs during sleep is required for a more complete understanding of how sleep influences cortical circuits. To this end, we investigated activity changes in the recently identified cortical layer 1 neuron-derived neurotrophic factor-positive (NDNF+) INs. This was accomplished using a combination of genetically encoded calcium imaging (GECI), miniature head mounted cameras, polysomnography, and GECI imaging in freely behaving mice. We find that NDNF+ INs are mostly active in rapid-eye-movement (REM) sleep and decrease their activity following total sleep deprivation. These results suggest that NDNF+ INs may play important roles in cortical EEG activity during REM sleep and compensatory changes following sleep loss.